Exploring Primary and Secondary Variants of Psychopathy in Adolescents in Detention and in the Community. Issue 5 (2nd September 2016) - Docherty, Meagan; Boxer, Paul; Huesmann, L. Rowell; O'Brien, Maureen; Bushman, Brad J.
Abstract : The current study aims to ascertain how different variants of callous–unemotional traits differ in their psychopathology, exposure to aggression and violence, and aggressive and violent behavior. If secondary/distressed variants (high in callous–unemotional traits and high in anxiety) and primary/traditional variants (high in callous–unemotional traits and low in anxiety) differ along these dimensions, it may speak to their different etiologies, treatment needs (e.g., trauma focused), and responsiveness to treatment. The current sample consisted of 799 adolescents from high schools ( n = 419) and juvenile detention centers ( n = 380). Participants were interviewed regarding their callous–unemotional traits, psychopathology, exposure to aggression and violence, and aggressive and violent behavior. Parents/guardians and teachers/staff members also reported on participants' callous–unemotional traits and aggressive and violent behavior. A model-based cluster analysis indicated that there were four clusters in the data set, based on callous–unemotional traits and anxiety: a nonvariant cluster, a primary/traditional callous–unemotional cluster, a secondary/distressed callous–unemotional cluster, and a "fearful" cluster. Secondary/distressed variants of psychopathy exhibited significantly greater symptoms of depression and psychoticism, more exposure to low level aggression and neighborhood violence, and more aggressive and violent behavior, as compared to the other clusters. Adolescents with callous–unemotional traits might not be a homogeneous group, but rather may differ in attitudes, behaviors, and exposure to risk, therefore differing in their treatment needs and responsiveness.